Penguatan Kapasitas Hukum Masyarakat dalam Menghadapi Transformasi Sertifikat Tanah Elektronik di Kabupaten Sumedang: Edukasi dan Pendampingan - Yulia, Aris; Anam, Saiful (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
This activity discusses the implementation of electronic land certificates as part of the digital transformation in Indonesia's land administration system. The transition from a manual to an electronic system presents various challenges, particularly in terms of accessibility, potential land disputes, and data protection. To address these obstacles, community service activities were carried out using a normative approach and case studies, targeting economically productive communities and vulnerable groups. The program's success was measured through several indicators, including increased legal awareness, the number of active users of the system, a reduction in land disputes, and compliance with data protection standards. This activity was held in Sukajaya Village, Sumedang Regency, West Java, on Friday, January 17, 2025, with participants consisting of village officials and residents of Sukajaya. The results indicate that synergy between clear legal regulations, continuous community assistance, and adequate technical support is the key to the successful implementation of electronic land certificates.